Evaluation of energy production using parabolic-dish solar collector: a case study of Iraq / Samir Gh Yayah, Ahmed Shihab Al-Samari and Itimad D J Azzawi - Yahya, Samir Gh; Yayah, Samir Gh; Al Samari, Ahmed Shihab; D.J. Azzawi, Itimad (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2023)
The parabolic dish reflector solar collector is one of the significant and most efficient steam-producing solar concentrating systems in thermoelectric power plants and, furthermore, it's considered to be environmentally friendly (renewable energy). Iraq has vast land for installing solar collectors to generate steam and use for thermal power plants. However, no such application/power plant has yet been built. Therefore, the proposed study investigates opportunities for using PDR solar collectors, including all advantages and challenges. To implement and estimate the productivity and efficiency of the PDR in (Diyala City / Iraq), a PDR solar collector with a total area of 0.708 m2 (including the glass pieces used as a reflective surface) was designed and fabricated. These glass pieces have been utilized to increase the reflection of solar rays by 80% when compared to a traditional case/setup. Two different systems (open and closed) were considered to investigate the performance of thermal power. The results show that the absorption temperature was increased from 34.6 to 95 °C. On the other hand, the coefficient of heat loss by convection increases by about (795.5 W). In addition, it was pointed out that the coefficient of total heat loss over time was increased by about 25 to 41% (closed and open systems). Furthermore, the experimental findings clearly demonstrate the usefulness of PDR solar heaters in Iraq.